Shell‐Isolated Nanoparticle‐Enhanced Electrochemiluminescence. Issue 39 (25th August 2022) - Lin, Long‐Hui; Wang, Jing‐Yu; You, Chao‐Yu; Qiu, Ling‐Hang; Lin, Jia‐Sheng; Zhang, Fan‐Li; Yang, Zhi‐Lin; Zhang, Yue‐Jiao; Chen, Xi; Li, Jian‐Feng
Abstract: Enhanced electrochemiluminescence (ECL) aims to promote higher sensitivity and obtain better detection limit. The core–shell nanostructures, owing to unique surface plasmon resonance (SPR) enabling distance‐dependent strong localized electromagnetic field, have attracted rising attention in enhanced ECL research and application. However, the present structures usually with porous shell involve electrocatalytic activity from the metal core and adsorption effect from the shell, which interfere with practical SPR enhancement contribution to ECL signal. Herein, to exclude the interference and unveil exact SPR‐enhanced effect, shell‐isolated nanoparticles (SHINs) whose shell gets thicker and becomes pinhole‐free are developed by modifying pH value and particles concentration. Furthermore, allowing for the distribution of hotspots and stronger enhancement, excitation intensity and ECL reaction layer thickness are mainly investigated, and several types of SHINs‐enhanced ECL platforms are prepared to fabricate distinct hotspot distribution via electrostatic attraction (submonolayer) and a layer‐by‐layer deposition method (monolayer). Consequently, the strongest enhancement up to ≈250‐fold is achieved by monolayer SHINs with 10 nm shell, and the platform is applied in a "turn‐off" mode sensing for dopamine. The platform provides new guidelines to shell preparation, interface engineering and hotspots fabrication for superior ECL enhancement and analytical application with high performance. Abstract : Shell‐isolated nanoparticles (SHINs) with pinhole‐free silica shell can exclude the interference from electrocatalytic activity and adsorption effect, allowing for exact SPR‐enhanced effect. Moreover, several types of SHINs‐enhanced ECL platforms are established to investigate the distribution of hotspots, expecting for stronger enhancement. Consequently, the strongest ECL enhancement up to ≈250‐fold is achieved, and the platform applies in sensing for dopamine.